2019
DOI: 10.3390/pr7020072
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Electric Potential Response Characteristics of Gas-Bearing Coal During Deformation and Fracturing Process

Abstract: Coal mass is deformed and fractured under stress to generate electrical potential (EP) signals. The mechanical properties of coal change with the adsorption of gas. To investigate the EP response characteristics of gas-bearing coal during deformation and fracture, a test system to monitor multi-parameters of gas-bearing coal under load was designed. The results showed that abundant EP signals were generated during the loading process and the EP response corresponded well with the stress change and crack expans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The minimum CSC period was introduced by Kalenkin. [39][40][41] He defined it as the time required for the coal to absorb oxygen in adiabatic conditions, to heat the coal, to release the water and gas from the coal, and to increase the temperature of the coal to the ignition temperature. He used this to establish a calculation model for the minimum CSC period:…”
Section: Influence Of the Advancing Speed On The Spontaneous Combusmentioning
confidence: 99%
“…The minimum CSC period was introduced by Kalenkin. [39][40][41] He defined it as the time required for the coal to absorb oxygen in adiabatic conditions, to heat the coal, to release the water and gas from the coal, and to increase the temperature of the coal to the ignition temperature. He used this to establish a calculation model for the minimum CSC period:…”
Section: Influence Of the Advancing Speed On The Spontaneous Combusmentioning
confidence: 99%
“…Previous studies show that the deformation and rupture process of a coal body can generate significant electric potential (EP) signals, and the EP response is closely related to the damage evolution process and stress state of the coal body [9,10]. Studying the EP response characteristics of a coal body during damage and failure processes can indirectly monitor the damage evolution process of a coal body and identify the precursor information of instability and failure of coal and rock mass [11]. Eccles et al observed abnormal signals of EP response before rock fracture under different experimental conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Shkuratnik et al [25] investigated the memory effects of AE by conducting uniaxial and triaxial cyclic unloading tests. With recent advancements in electronic technologies and high-speed photography, several modern techniques for rock mechanics research have been commonly adopted in the recent years [26], for example, electromagnetic radiation technology [27,28], scanning electron microscope, infrared thermal image technology [29], and electrical resistivity technology [22]. However, the application of these technologies is limited to the study of coal and rock damage/failure, while the influence of water content and soaking is rarely considered.…”
Section: Introductionmentioning
confidence: 99%